Short Communication:Geographic distribution and conservation status of the bay cat Catopuma badia, a Bornean endemic - Mohd-Azlan, J.; Sanderson, Jim (Cambridge University Press, 2007)
Despite being one of the rarest felids in the world the Endangered Bornean bay cat Catopuma badia has received little conservation attention. Most information consists of historical records, morphological descriptions, and anecdotes from various sources. During 2003–2006 we undertook surveys using camera trapping, interviews and field observations, to determine the species’ distribution and document any threats to its persistence. We also examined museum specimens and completed a thorough literature review, collecting 15 additional geographic records throughout Borneo. Our results show that opportunistic hunting and land use changes are the main threats to the bay cat, and we make recommendations for its conservation.